Factors influencing the retention of international IT talent: An empirical investigation in Singapore - Osman-Gani, AAhad M.; Paik, Yongsun (Inderscience Enterprises Ltd., 2016)
In today's global war for corporate business talent, organisations have emphasised attraction methods. But retention of talent - particularly in the competitive IT sector - has not received much attention. The high turnover of talent is increasingly becoming a challenging issue for organisational management, especially for HR professionals. In this regard HRD strategies can play significant roles in helping organisations to win the talent war. Research in this area is scarce. This paper presents the results of an empirical study on the identification of major factors contributing to the retention of international IT talent in Singapore, one of the most vibrant economies of Asia where attraction and retention of IT talent has been an issue of high priority. Among the top five factors, opportunities for training and skills development and career development issues were identified. Implications of the findings are discussed for organisational policy decisions and for future research.